2022
DOI: 10.1002/ange.202201104
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Corrole‐Based Porous Organic Polymers for Electrocatalytic Oxygen Reduction and Evolution Reactions

Abstract: Integrating molecular catalysts into designed frameworks often enables improved catalysis. Compared with porphyrin‐based frameworks, metal‐corrole‐based frameworks have been rarely developed, although monomeric metal corroles are usually more efficient than porphyrin counterparts for the electrocatalytic oxygen reduction reaction (ORR) and oxygen evolution reaction (OER). We herein report on metal‐corrole‐based porous organic polymers (POPs) as ORR and OER electrocatalysts. M‐POPs (M=Mn, Fe, Co, Cu) were synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…60,61 Halogen-substituted poly-porphyrins, poly-phthalocyanines, and poly-corroles specifically those with F, Cl, and Br at the edge positions, have been widely studied. 62,63 The introduction of halogen substituents helps to adjust the electron density of the polymer. The interaction between the active centres and the intermediates can be appropriately optimized based on the DFT calculations.…”
Section: Molecular Engineering Of Electrocatalytic Active Centresmentioning
confidence: 99%
“…60,61 Halogen-substituted poly-porphyrins, poly-phthalocyanines, and poly-corroles specifically those with F, Cl, and Br at the edge positions, have been widely studied. 62,63 The introduction of halogen substituents helps to adjust the electron density of the polymer. The interaction between the active centres and the intermediates can be appropriately optimized based on the DFT calculations.…”
Section: Molecular Engineering Of Electrocatalytic Active Centresmentioning
confidence: 99%
“…Yang and his group have reported Ni–Fe-incorporated porphyrin-based porous organic polymer (POP) for oxygen evolution reaction . Cao et al showed OER and ORR activities of metal-corrole-based POP . There are other examples, where researchers have put efforts into designing some noble metal-based catalysts. In our recent efforts to explore the catalytic activity of porphyrin-based polymers, we have reported a urea oxidation reaction (UOR) and nonenzymatic glucose sensing using metal-incorporated porphyrin-based polymers.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] For prospective PEC performance, designing and developing a highly effective and stable catalyst is crucial. Various materials as electrocatalysts [16][17][18][19] and photoelectrocatalysts [20] have been explored and optimized to enhance their efficiency using different strategies. A key challenge is to find novel, low-cost, and durable photocatalysts with suitable band positions.…”
Section: Introductionmentioning
confidence: 99%